Electrodeposition and Corrosion Resistance Properties of Zn-Ni/TiO2 Nano composite Coatings - B. M. Praveen; T. V. Venkatesha (International Journal of Electrochemistry)
Nano sized TiO2 particles were prepared by sol-gel method. TiO2 nano particles were dispersed in zinc-nickel sulphate electrolyte and thin film of Zn-Ni-TiO2 composite was generated by electrodeposition on mild steel plates. The effect of TiO2 on the corrosion behavior and hardness of the composite coatings was investigated. The film was tested for its corrosion resistance property using electrochemical, weight loss, and salt spray methods. The paper revealed higher resistance of composite coating to corrosion. Microhardness of the composite coating was determined. Scanning electron microscope images and X-ray diffraction patterns of coating revealed its fine-grain nature. Average crystalline size of the composite coating was calculated. The anticorrosion mechanism of the composite coating was also discussed.